Identification of stroke-associated-antigens via screening of recombinant proteins from the human expression cDNA library (SEREX) - Machida, Toshio (J Transl Med, 2015)
BACKGROUND: Because circulating antibodies against a variety of antigens have been detected in patients with coronary heart disease, carotid atherosclerosis and those who have suffered a stroke, it is suspected that immune response may be one of the mechanisms of atherogenesis The objective of this study is to identify novel antibodies in ischemic stroke patients by screening the expressed recombinant proteins using a human cDNA library (SEREX). METHODS: To identify the candidate antigens, cDNA library was screened by SEREX using plasma from ten patients with ischemic stroke. Subsequently, via ELISA using recombinant proteins and synthetic peptides, the serum antibody levels were measured in two independent patient/healthy donor (HD) cohorts (142 and 78 in the 2nd screening and a validation cohort, respectively). RESULTS: The initial screening resulted in the identification of six candidate antigens. Of these antigens, replication protein A2 (RPA2) was determined to be the antigen associated with stroke (P < 0.05) by ELISA with 2nd screening and validation cohort. Multifactorial logistic regression analysis showed that the increased levels of the RPA2 antibodies (RPA2-Abs) associated with stroke independent of other risk factors for stroke (P < 0.05). Receiver operating curve analysis demonstrated that the area under the curve from ELISA using GST fusion RPA2 and synthetic peptides (bRPA2-132) were 0.867 (95% CI: 0.798-0.936) and 0.971 (95% CI: 0.940-1.00), respectively. If the cut-off value of the bRPA2-132-Ab level was determined to be 0.334, the sensitivity and specificity of the antibody level as the diagnostic marker for stroke were 0.323 (95% CI: 0.209-0.453) and 1.00 (95% CI: 0.713-1.00), respectively. CONCLUSIONS: SEREX identified RPA2 as the antigen associated with ischemic stroke and serum auto-antibodies against RPA2 elevates in stroke patients. RPA2-Abs could become a biomarker for the evaluation of ischemic stroke at risk.